Measuring regional innovation in one dimension: More lost than gained? - Matthias Siller; Christoph Hauser; Janette Walde; Gottfried Tappeiner (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2015)
In both academic literature and political discussions the concept of innovation is recognized as an essential ingredient in economic development and competitiveness for firms, regions, and nations. Innovation also ranks at the top of policy agendas in the field of regional policy. Therefore, the attractiveness of an appropriate innovation index for ranking regions and further developing them along a more or less objective measurement scale is evident. However, whether such rankings help convey a better understanding of innovation and its drivers, or whether they are merely a special type of 'beauty contest' with little substance is the focus of our analyses. To deny the latter, the innovation output indicators used for the composite index have to be appropriate representatives of the underlying innovation concept and each indicator has to be driven by the same impact factors. If this is not the case, interpretation of the index inevitably gives rise to partly inappropriate policy recommendations. In order to demonstrate this claim we elaborate a set of innovation indicators at the regional level based on the theoretical concept of the OECD document 'The Measurement of Scientific and Technological Activities, Proposed Guidelines for Collecting and Interpreting Technological Innovation Data' known as the 'Oslo Manual' (OECD, 2005) and their empirical implementation in the Community Innovation Survey. Additionally, innovation drivers well established in the literature are collected to estimate their impact on each innovation indicator as well as on the composite index derived from the innovation indicators. The question whether 2 innovation should be measured as a multidimensional concept and investigated using various indicators or whether simplifying innovation to a one-dimensional concept is appropriate is clearly answered in favour of the multidimensional approach. Surprisingly, this is not due to the multidimensionality of the indicators themselves (all statistical measures indicate that the considered variables are sufficiently represented by one component), but to our first evidence that the innovation output indicators are driven by various impact factors and can therefore be influenced by various political strategies. According to these findings any type of innovation ranking is of very limited use.
Keywords: R11; O31; O33; 330; Regional innovation; Innovation dimensions; Patent applications; Community Innovation Survey